TESTING OUT TRANSLATION UNIVERSALS IN LEGAL TRANSLATION: QUANTITATIVE INSIGHTS FROM A PARALLEL CORPUS OF SPANISH CONSTITUTIONAL COURT’S JUDGMENTS TRANSLATED INTO ENGLISH - Pontrandolfo, Gianluca (Comparative Legilinguistics, 2020)
Research into ‘translation universals’ in legal translation is a relatively new field, which still needs to be expanded with further empirical studies. The few studies conducted so far fall into two main categories: a) analyses that explore the typical features of European legalese as translated language against national legal language; b) studies based on corpora of national legal language translated into other national languages (see Pontrandolfo 2019a:20-22). The present paper is framed within the second category and aims at contributing to the academic debate on translation universals applied to legal language; more specifically, it aims at testing the methodology adopted to study translation universals on a bilingual parallel corpus of judgments delivered by the Spanish Constitutional Court (Tribunal Constitucional, TC) translated for informative purposes into English. The corpus-based analysis, carried out mainly quantitatively, includes the comparison with a larger corpus of original judgments delivered by the UK Supreme Court (UKSC) with the final objective of testing some indicators of simplification, explicitation, normalisation, levelling out, interference, untypical collocation (see Zanettin 2012: 11-25). Preliminary results are promising, even though it is not possible to identify robust and homogeneous trends.